Ketogenic Diet in Super-Refractory Status Epilepticus - Garnett Smith; Craig A. Press (Pediatric Neurology Briefs Publishers, 2017)
Researchers from the Children's National Health System in Washington, D.C. studied the feasibility, rate of complications, and effect on seizures of initiating the Ketogenic Diet (KD) in pediatric patients with Super-Refractory Status Epilepticus (SRSE).